Enhancing the photocatalytic efficiency of two-dimensional aluminum nitride materials through strategic rare earth doping - Yan, Weiyin; Yan, Yayu; Wang, Zirui; Li, Qiao-Hong; Zhang, Jian (Physical chemistry chemical physics : PCCP, 2023)
Two-dimensional (2D) materials demonstrate promising potential as high-efficiency photocatalysts. However, the intrinsic limitations of aluminum nitride (AlN), such as inadequate oxidation capacity, a high carrier recombination rate, and limited absorption of visible light, pose considerable challenges. In this paper, we introduce a novel co-doping technique with dysprosium (Dy) and carbon (C) on a 2D AlN monolayer, aiming to enhance its photocatalytic properties. Our first-principles calculations reveal a reduction in the bandgap and a significant enhancement in the visible light absorption rate of the co-doped Al 24 N 22 DyC 2 structure. Notably, the distribution of the highest occupied molecular orbital and the lowest unoccupied molecular in proximity to Dy atoms demonstrates favorable conditions for carrier separation. Theoretical assessments of the hydrogen evolution reaction and oxygen evolution reaction activities further corroborate the potential of Al 24 N 22 DyC 2 as a competent catalyst for photocatalytic reactions. These findings provide valuable theoretical insights for the experimental design and fabrication of novel, high-efficiency AlN semiconductor photocatalysts. A novel Dy, C co-doped material on 2D AlN monolayer is introduced. DFT calculations show that the bandgap of Al 24 N 22 DyC 2 decreases, absorption rate of visible light and catalytic activities of HER and OER increases significantly.